Human Resource Development Through KYT Training (Kiken Yochi Training) To Improve Employee Performance at PT. Nichias Rockwool Indonesia (Autopart) - Siti Hasnah Rosmiyati; Wike Pertiwi; July Yuliawati (Enrichment : Journal of Management, 2022)
This study aims to describe human resource development through KYT training (kiken yochi training) to improve employee performance at PT. Nichias Rockwool Indonesia (autopart). The analytical method used in this research is literature study, case study and documentation. The research approach used in this research is descriptive qualitative. The results of this study are the performance of employees at PT. Nichias Rockwool Indonesia (Autopart) has been carried out and is improving by conducting KYT training activities. This KYT training aims to reduce the level of work accidents in the work environment, prevent the occurrence of human errors, reduce the level of potential hazards in the work environment and increase the level of employee alertness to abnormal situations and conditions.